Site-Directed Mutagenesis of Glu-269 L-Arabinose Isomerase from Geobacillus stearothermophilus Isolated from Tanjung Api Poso, Indonesia - Fitriani, Dewi; Wulandari, Puspita Suci; Saksono, Budi (BRIN, 2010)
Industrializing of tagatose requires enzymes that meet to industrial need such as thermophile, slightly acidic and metal independent. Previously, we cloned, sequenced and expressed L-arabinose isomerase from Geobacillus stearothermophilus isolated from Tanjung Api, Poso, Indonesia. Based on DNA alignment analysis, the gene had high homology with those of G. stearothermophilus T6 (Gene Bank Acc No: AAD45718) which has optimum activity at high temperature and alkaline condition. In this paper, we described site-directedmutagenesis approach to mutate Glu-269 (Q269) to Lys-269 (K269) to decrease the optimum pH of the strain. Sequencing result showed that mutagenesis had been successful to mutate amino acid at position 269 from glutamine (Q) into lysine (K). Expression of mutant Q269 showed protein with molecular mass 56 kDa.